Editorial: A Special Issue - Campbell, Leith H. (Journal of Telecommunications and the Digital Economy, 2023)
This editorial introduces the June issue, which includes a main Special Issue section on Women’s Participation in the Digital Economy and Digital Society, as well as papers from the general submissions.